Implementation of SSOP (Standard Sanitation Operating Procedure) in Freezing Process Cuttlefish (Sepia officinalis) in PT. Karya Mina Putra, Rembang, Central Java - Erni Ristyanti; Endang Dewi Masithah (Universitas Airlangga, 2021)
Quality deterioration is susceptible by marine products, so that proper handling and processing is needed to delay the activity of pathogenic bacteria. The procedure of handling marine products must be done carefully and fulfill the SSOP requirements to minimize contamination products by eliminating or controling the factors that cause contamination from raw material until the products ready for distribution. Praktek Kerja Lapang was held in PT. Karya Mina Putra, Rembang, Central Java on December 23, 2019 to January 23, 2020. The method that used are descriptive method with data collection includes primary data and secondary data. The data is collected by observation, interview and active participation. Some SSOP requirements in the cuttlefish freezing process at PT. Karya Mina Putra have been fulfilled although there are some obstacles in the application of personal hygiene and damage to the foot sink in several last times. These obstacles can cause contamination to the product and reduce the productivity of the food processing unit.